2021
DOI: 10.1177/10760296211000129
|View full text |Cite
|
Sign up to set email alerts
|

FM Combined With NIHSS Score Contributes to Early AIS Diagnosis and Differential Diagnosis of Cardiogenic and Non-Cardiogenic AIS

Abstract: A growing researchers have suggested that fibrin monomer (FM) plays an important role in early diagnosis of thrombotic diseases. We explored the application of FM in the diagnosis and classification of acute ischemic stroke (AIS). The differences in FM, D-dimer, and NIHSS scores between different TOAST (Trial of ORG 10172 in Acute Stroke Treatment) types were analyzed with one-way ANOVA; the correlation between FM, D-dimer and NIHSS score in patients with different TOAST classification was analyzed by Pearson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Similar results were obtained by H Y et al, who suggested that increased SBP mediates brain-blood barrier damage and upregulation of aquaporin Protein-4 via oxidative stress, leading to an increased risk of neurological deterioration (18). Meanwhile, hypertension impairs collateral circulation, reduces the ability of brain tissue to maintain adequate oxygenation during cerebral artery occlusion, and promotes the accumulation of reactive oxygen species and the release of in ammatory factors, leading to further damage to the blood-brain barrier, which in turn leads to hemorrhagic transformation after thrombolysis (19).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by H Y et al, who suggested that increased SBP mediates brain-blood barrier damage and upregulation of aquaporin Protein-4 via oxidative stress, leading to an increased risk of neurological deterioration (18). Meanwhile, hypertension impairs collateral circulation, reduces the ability of brain tissue to maintain adequate oxygenation during cerebral artery occlusion, and promotes the accumulation of reactive oxygen species and the release of in ammatory factors, leading to further damage to the blood-brain barrier, which in turn leads to hemorrhagic transformation after thrombolysis (19).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, patients with cardiogenic embolism also have a larger cerebral infarct area and a more rapid progression of the disease due to the sudden onset of the disease and the fact that collateral circulation has not yet formed at the infarct site. [30] The occurrence of AIS causes cerebral edema, which exacerbates the patient's condition and promotes an increase in intracranial pressure, exacerbating neurological impairment. However, the correlation between cardiogenic embolism and the occurrence of END after AIS was not found in this study, and it is considered that due to the inclusion of a small sample size of cardiogenic embolism (n = 73), further multicenter studies with large data samples are needed for validation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by He et al who suggested that increased SBP mediates brain–blood barrier damage and upregulation of aquaporin Protein-4 via oxidative stress, leading to an increased risk of neurological deterioration ( 19 ). Meanwhile, hypertension impairs collateral circulation, reduces the ability of brain tissue to maintain adequate oxygenation during cerebral artery occlusion, and promotes the accumulation of reactive oxygen species and the release of inflammatory factors, leading to further damage to the blood–brain barrier, which in turn leads to hemorrhagic transformation after thrombolysis ( 20 ).…”
Section: Discussionmentioning
confidence: 99%